Restoring the balance : a Middle East strategy for the next president - Haass, Richard N. (Brookings Institution Press, 2008)
Experts from the Brookings Saban Center and Council on Foreign Relations propose a new, nonpartisan strategy drawing on the lessons of past failures to address short-term and long-term challenges to U.S. interests. Issues and policy recommendations cover the Arab-Israeli conflict, counterterrorism, Iran, Iraq, political and economic development, and nuclear proliferation.